“Evaluación de dos métodos de siembra, interaccionados con quelatos a base de microelementos, sobre el rendimiento del cultivo de arroz bajo condiciones de secano”. - Morán Mariscal, Darwin José (2019)
SUMMARY The experimental work was developed in the lands of Mr. Humberto Ismael Icaza Sánchez, via Baba, Rcto. San Ignacio. The geographic coordinates are 197165.89 UTM south latitude and 351695.02 UTM west longitude, 8 msmm. The zone possesses humid tropical climate, annual temperature of 24.90 0C, annual precipitation 2,037.00 mm, average evaporation of 1128.90 mm, humidity 79% and 725.10 hours of annual heliophany. The soil that owns the land is of flat topography, clay loam texture and regular drainage. The "SFL-09" rice seed was used as seed material. The treatments were constituted by the methods of sowing to the volley and continuous stream and like chelated products Folcrop Ca - B; Folcrop Combi Fe - Mn - Zn; Folcrop Ca - B - Fe - Mn - Zn all in doses of 2.0 L / ha and a control without application of product. The experimental design of Random Complete Blocks was used in factorial arrangement A x B, where Factor A was the planting methods and Factor B the products based on chelates and control with its respective dose and three repetitions. The comparison of the averages was carried out according to the Tukey Test. The plots had dimensions of 5.0 m wide and 6.0 m long, given a total test area of 800 m2. All the practices and agricultural work that the crop needs for its normal development were carried out, such as land preparation, sowing, weed control, irrigation, fertilization, phytosanitary control and harvesting. Based on the results obtained, it was determined that the two sowing methods, interacted with chelates based on microelements, influenced the rice crop yield under rainfed conditions; the chelated products promoted the longest flowering time in the rice variety "SFL - 09"; broadcasting, using Folcrop Ca - B - Fe - Mn - Zn reported higher average plant height, number of tillers and panicles / m2, length of panicles, grains per panicles and weight of 1000 grains and the highest yield of the crop and net profit was reported with the broadcast sowing method with Folcrop Ca - B - Fe - Mn - Zn chelated product with 5177.1 kg / ha and $ 351.37. Keywords: rice, planting methods, chelates, yield.